A Short Review on Phytoconstituents from Genus Albizzia and Erythrina (Bangladesh Pharmaceutical Journal, 2018)
The genus Albizzia and Erythrinaare the leading sources of phytoconstituents. The aim of this review is to solicitude of the phytoconstituents from some medicinal plants of these genus. A total nine medicinal plants were studied and 121 chemical constituents along with structures have been reported here. Erythrina burttii consists of highest number of constituents.Bangladesh Pharmaceutical Journal 21(2): 160-172, 2018